Dolok Sanggul Business Hotel (Sustainable Architecture) - Nurlisa Ginting; Ivo Michael Padang (Talenta Publisher, 2017)
The business hotel is one of the facilities that support business work, and their activities are the reason of humans to travel some place for business in an area or urban areas. Dolok Sanggul Kab. Humbang Hasundutan is the one of area increasing their economy in every year with agriculture and hospitality sector as one of the driving axis of the economy in this area but, no one the hotel that supports business activities in around of this area. As one of the efforts undertaken to maintain the sustainability of natural, the design of Sustainable Architecture in the business hotels to be designed is very suitable theme be the reference to scheming business hotels in this area.